Relationship Between Soil Physical Characteristics and Infiltration Rate of The Practice Area of SMK PPN Banjarbaru - Fitriati, Ulfa; Rahman, Kholiq Malikur (Fakultas Teknik Universitas Brawijaya, 2023)
The practice area for the Banjarbaru State Agricultural Development Vocational School (SMK PP N Banjarbaru) is located in Kemuning Village, South Banjarbaru District, Banjarbaru City, South Kalimantan Province. Regarding the land use in the research location, the majority is used for plantation land, which is one of the lands suitable for water catchment areas in Banjarbaru City. The Practice Land of PP N Banjarbaru Vocational School is one of the models of good catchment area land from good land use and irrigation systems. Conducted this analyze the infiltration rate and its influence on the physical properties of the soil. From the results of the infiltration test using a double ring infiltrometer which was then analyzed using the Horton method, the most considerable infiltration rate was in open land, namely 33.83 cm/hour, rubber plantations of 22.57 cm/hour, on palawija land it is 15.57 cm/hour and on mahogany land, it is 14.47 cm/hour. From the results of the analysis using the linear regression approach, the physical properties of the soil that can affect the infiltration rate include 16.7% bulk density, 75% permeability, and 90% moisture content. Meanwhile, particle density and porosity only affect 0.7% and 3.5%.